PENGARUH RELATIONSHIP MARKETING TERHADAP LOYALITAS PENGGUNA JASA KURSUS ONLINE “Studi tentang Loyalitas Pengguna Kursus Online pada Nuraz Institute, Tarakan” - Deni Marsha (LPSDI Bina Patria, 2024)
The purpose of this study is to analyze and determine the effect of relationship marketing on user loyalty for online course at the Nuraz Institute, Tarakan. The method used in this research is quantitative with an explanatory approach. The population in the study included all users of the online course at the Nuraz Institute with a saturated sample of 33 respondents. The data analysis technique used is the regression analysis which aims to determine the effect of the relationship marketing variable toward the user loyalty. The results showed that there was an influence of relationship marketing towards user loyalty for online course at the Nuraz Institute. The relatioship marketing has a very strong influence towards customer loyalty. Marketing and user loyalty in the business world play an important role to running a business, especially in the service provider business.